ON THE STABILITY BY ACTING FORCE WITH PAIR IMAGINING ROOTS FOR THE SECOND ORDER SYSTEM - Hambardzumyan, S. R. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2003)
The problem of stability of system for second order of non-linear differential equations in critical case has been considered, when the characteristic equation, corresponding to linear approximation of system, has pair imagining roots. Sufficient conditions have been obtained in case of which the trivial solution of the considered system is either asymptotic stable or non-stable for acting force.
Keywords: system for second order of non-linear differential equations; acting force; linear approximation